THE EFFECT OF PROBLEM POSING APPROACH TOWARDS STUDENTS’ MATHEMATICAL DISPOSITION, CRITICAL & CREATIVE THINKING ABILITY BASED ON SCHOOL LEVEL - Nurjaman, Adi; Sari, Indah Puspita (Jurnal Infinity, 2017)
The background of this study is the school of the new students of mathematics education courses came from grade high, medium and low. Here the writer wants to see how much influence of the school level on new students’ critical thinking skills and creative mathematical. The purpose of this study was to examine differences in new students’ mathematical disposition, critical & creative thinking ability through the mathematical problem posing approach based on school level (high, medium, low). The method used in this research is the experimental method, with only posttest design. The population of this study is all the students of mathematics education department in Cimahi; while the sample is selected randomly from one college. Then from this chosen college is taken two samples from random class. The instrument of essay test is used to measure students’ critical and mathematical creative thinking ability; while non-test instrument is questionnaire of attitude scale. The results show that: 1) based on the school level (high, medium, and low); there is difference in students’ mathematical critical thinking ability through problem posing approach. 2) based on the school level (high, medium, and low); there is difference in the students’ mathematical critical thinking ability through problem posing approach. 3) based on the school level (high, medium, and low); there is difference in students’ mathematical disposition.